Whose property? : the deepening conflict between private property and democracy in Canada - Vogt, Roy (University of Toronto Press, 1999)
Vogt shows that many diverse and contentious subjects - including aboriginal struggles, threats to the environment, and the distribution of power in the workplace - turn on the question of how property rights should be defined and distributed.